Extent and implications of incorrect offspring-sire relationships in pastoral production system in Kajiado District, Kenya - Maichomo, M.W.; Gitau, G.K.; Gathuma, J.M.; Ndung'u, J.M.; Kosura, O.; Olivier, H.O. (2008)
The aim of this study was to evaluate accuracy of farmer's paternity identification which determines success of future breed selection and hence genetic gain. Paternity of 269 Orma/zebu and Sahiwal/zebu calves was evaluated using genetic markers and the likelihood based method. Results indicate that only 6.7% farmer alleged paternities were confirmed, 88% parent-offspring relationships were rejected and 18% parent-offspring relationships were undetermined. However, 82% of offsprings were assigned at least 80% confident paternities to one of the sampled candidate males. These results suggest that there is need to institute proper breeding program in the pastoral area if farmers are to benefit from their current efforts of breed improvement.